Iktomi and the boulder : a Plains Indian story - Goble, Paul. (New York : Orchard Books, 1988)
Iktomi, a Plains Indian trickster, attempts to defeat a boulder with the assistance of some bats, in this story which explains why the Great Plains are covered with small stones.
"References": p. [4].
Wilson's Children.
School Library Journal starred.
Notable/Best Books (A.L.A.).
4.7
K-3
Keywords: Dakota Indians -- Folklore; Indians of North America -- Great Plains -- Folklore; Dakota Indians -- Folklore; Indians of North America -- Great Plains -- Folklore; Dakota Indians -- Legends; Native Americans -- Great Plains; Native Americans -- North America -- Great Plains; Native Americans -- United States -- Great Plains; Dakota Indians -- Legends; Indians of North America -- Great Plains -- Legends